Use of thermogenic supplements based on caffeine and factors associated with quality of life related to health in physical activity practitioners - Gomes, Camila Bebert (2014)
The aim of this study was to evaluate the association between the use of thermogenic supplements the basis of caffeine and associated factors related to quality of life (HRQoL) in physically active for a health Salvador.127 students practicing physical activity, of both genders, were evaluated during September and October 2010, through the Quality of Life Questionnaire SF-36.After analysis, 39 (30.7%) reported having used or thermogenic supplementscaffeine based, with 11 males (28.2%) and 28 (71.8%) were female.The mean age of the sample was 20-25 years (61.5%).According to the Education, (56.4%) of the participants were enrolled in higher education.Of the respondents, 56.4% stated that the supplement helped in weight loss, increased 20.5% in the physical layout, the same value was found for those who had better performance in training and 12.8% reported greater muscle definition.The domains of HRQOL were more committed Mental Health (52%), general health (62%) and functional capacity (56%).As the above results shows, seems to be no associations between HRQoL and the use of thermogenic which leads to the need for new studies to fill this knowledge gap.